2013
DOI: 10.3390/ijms14058832
|View full text |Cite
|
Sign up to set email alerts
|

LILRA3 Is Associated with Benign Prostatic Hyperplasia Risk in a Chinese Population

Abstract: A recent prostate cancer (PCa) genome-wide association study (GWAS) identified rs103294, a single nucleotide polymorphism (SNP) located on LILRA3, a key component in the regulation of inflammatory inhibition, to be significantly associated with PCa risk in a Chinese population. Because inflammation may be a common etiological risk factor between PCa and benign prostatic hyperplasia (BPH), the current study was conducted to investigate the association of rs103294 with BPH risk. rs103294 was genotyped in a Chine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
0
11
1
Order By: Relevance
“…Three SNPs, rs12621278 in ITGA6 at 2q31, rs339331 in RFX6 at 6q22, and rs103294 in LILRA3, were also significantly associated with BPH risk [10, 11]. More importantly, we found that rs12621278 and rs12653946 at 5p15 were significantly associated with BPH aggressiveness [10].…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Three SNPs, rs12621278 in ITGA6 at 2q31, rs339331 in RFX6 at 6q22, and rs103294 in LILRA3, were also significantly associated with BPH risk [10, 11]. More importantly, we found that rs12621278 and rs12653946 at 5p15 were significantly associated with BPH aggressiveness [10].…”
Section: Discussionmentioning
confidence: 94%
“…The detailed clinical characteristics of all subjects were described in detail in our previous study [9, 10]. Briefly, age distribution was significantly different between cases and controls ( P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations